A Study on the Effect of Housing on Physiological Responses of Nellore Lambs Kasala (Indian Journal of Animal Production and Management, 2024)
A study was carried out to find out the effect  of housing on physiological responses of Nellore  Jodipi lambs under tropical environmental  conditions. Thirty weaned Nellore ram lambs of 3-4  months age were selected based on body weight  (average initial body weight) and randomly divided  into three groups of ten animals each. The lambs in  Group-I were housed with morum flooring and  asbestos roofing with tree shade, while Group-II  lambs were housed with morum flooring and  asbestos roofing without tree shade and Group-III  lambs were housed with elevated slatted flooring  and galvalume roofing without tree shade.  Temperature and humidity values were significantly  (P
Keywords: Nellore lambs; slatted flooring; asbestos roofing; tree shade; physiological responses